2019
DOI: 10.3892/ol.2019.10839
|View full text |Cite
|
Sign up to set email alerts
|

Generation and identification of a thyroid cancer cell line with stable expression of CCDC67 and luciferase reporter genes

Abstract: Coiled-coil domain containing 67 (CCDC67) gene is a tumor suppressor gene that exhibits a significant inhibitory effect on a variety of tumors. Our previous study demonstrated that the upregulation of CCDC67 gene in TPC-1 cells inhibited cell proliferation, migration and invasion, and promoted apoptosis in vitro. However, due to the lack of a suitable cell tool, these results were not validated in vivo. In the present study, a thyroid cancer cell line with stable expression of CCDC67 and luciferase reporter ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…RAS mutations are priority to combine with phosphorylated AKT in thyroid cancer [12,14].Studies have found that with the accumulation of mutated genes and the activation of two pathways, differentiated thyroid cancer can continue to progress to poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC) [15]. And gene mutations (including TP53, CTNNB1 and ALK mutations) further accelerate the occurrence and development of this process [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…RAS mutations are priority to combine with phosphorylated AKT in thyroid cancer [12,14].Studies have found that with the accumulation of mutated genes and the activation of two pathways, differentiated thyroid cancer can continue to progress to poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC) [15]. And gene mutations (including TP53, CTNNB1 and ALK mutations) further accelerate the occurrence and development of this process [16][17][18].…”
Section: Introductionmentioning
confidence: 99%